POSISI PARALON DAN BERBAGAI KONSENTRASI PUPUK PELENGKAP AIR (PPC) PADA PERTANAMAN KAILAN (Brassica alboglabra) DENGAN SISTEM BUDIDAYA VERTIKULTUR - Fitrianza, Danti; Yulia, Arnis En; ', Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Kailan (Brassica alboglabra) are vegetables that beneficial to human health because it can help digestion, neutralize acidity and prevent disease. Kailan cultivation is closely related to fertilization and cultivation technical factors. One of fertilizers that can provide nutrients for plants kailan is a liquid fertilizer. Agricultural land is increasingly narrow lead farmers, especially those living in urban areas should make efficient use of land in order to achieve maximum production, one of the ways that can be done to address the problem of limited land is cultivated verticulture system. The research aims to determine the effect of paralon positions and provision of various concentrations of complementary liquid fertilizer and to know the paralon position combination with complementary liquid fertilizer concentration appropriate to plant growth kailan (Brassica alboglabra) with verticulture cultivation system. The experiment was conducted at the home screen experimental garden of the Faculty of Agriculture, University of Riau for 3 months, from August to October 2014. The experiment was conducted by using a split plot design (Split Plot Design). The main plot is a variety of positions paralon (P), which consists of three levels: P1:Position paralon top (height 120 cm), P2: paralon middle position (height 80 cm), P3: Position paralon under (height 40 cm). The subplots are complementary liquid fertilizer concentration (B) consists of 4 levels: B0: Without fertilizer(control), B1: Fertilizers liquid complementary 1 cc/l water, B2: Fertilizers liquid complementary 2cc/l, B3: Fertilizers complementary liquid 3cc /l. The results showed that the combination treatment paralon position as the main plots and complementary liquid fertilizer as subplots provide no real effect on all parameters. Single factor paralon top position (120 cm) as well as complementary liquid fertilizer at a dose of 3 cc / l water can increase plant height, number of leaves, stem diameter, fresh weight, weight suitable for consumption and plant dry weight kailan. Keyword: kailan, paralon position, supplementary liquid fertilizer, verticulture